Microstructural and Mechanical Behaviors of Friction Stir Welded Dissimilar AA6082-AA7075 Joints. (22nd September 2021) - Vetrivel Sezhian, M.; Giridharan, K.; Peter Pushpanathan, D.; Chakravarthi, G.; Stalin, B.; Karthick, Alagar; Manoj Kumar, P.; Bharani, Murugesan
Abstract : In this research, microstructural events and mechanical behaviors in dissimilar friction stir welding (FSW) of aluminium (Al) alloy AA6082-AA7075 joints have been evaluated to apply aerospace, defense, and military sectors. FSW parametric effects have a more significant impact on the mechanical performances and microstructure of produced joints. FSW tool rotational speed, welding speed, and tool plunge speed were chosen to make the weld joints. The rotational tool speeds of 1600 rpm and 2300 rpm, welding speeds of 40 mm/min and 60 mm/min, and tool plunge speeds of 20 mm/min and 30 mm/min were set as the upper and lower limits. A constant axial force of 5 kN was maintained throughout the joint fabrication process. A taper pin-profiled tool was utilized to produce the butt welded joints. Mechanical properties of microhardness, tensile strength, yield strength, elongation, and bending strength of the joints were analyzed. The response of the stir zone microstructure to processing parameters was evaluated using optical microscopy (OM) and fractographic analysis of a tensile specimen shown by scanning electron microscope (SEM). The weld joints produced at 2300 rpm, tool traveling rate of 40 mm/min, and tool plunge speed of 30 mm/min showed the greatest tensile strength of the 191 MPa hardness of 145 Hv at the weld center and also the maximum bending strength of 114.23 N/mm 2 was achieved. The lowest bending strength of 25.38 N/mm 2 was obtained at 1600 rpm with 60 mm/min due to inappropriate mixing of the base metals and poor joint quality. Furthermore, this study revealed that a higher tool plunge speed facilitates the formation of equiaxed grains in the thermomechanically affected zone (TMAZ) on the advancing side (AS). Additionally, the increment in tool rotational speed significantly improved the tensile strength, weld joint quality, and joint efficiency.